A Novel Hybrid Multilevel Inverter with Switch Reduction - P.Meenalochini, S. Syed Abdul Haq, R.Mohammed Abdullah, T.Harish Babu, Abdul Kareem.M, R.Karthick (International Journal of Advanced Science and Technology, 2020)
A layer inspired inverter topology with decreased number of power switches is proposed. This paper proposes a novel single stage fell summarized decreased switch based creamer MLI game plan that can make the most prominent number of yield voltage relevant to both symmetric similar to disproportionate sources of DC voltage. An epic single-stage cream MLI was made using the least number of portions of force contraptions. An interesting section of proposed topology is that similarly hardly any plate-equivalent relationship of MLI inverter in structure bound system could be summarized to n-levels. A stunned inverter is an electronic power contraction used for high voltage and high power use of low trading nerves and lower total consonant bending, thereby reducing the size and lion share of uninvolved channels. This new topology is based on a blend of custom diode cutting and topologies associated with H. The proposed idea has achieved high-power evaluations just as it requires the use of the realistic source of influence. It dramatically decreases the adversities of trading; the sounds of cost and low persuasion and along these lines increase the hard and fast symphonic bending. The working nuances of the system and structure of this proposed stunned inverter structure are delineated and checked through the results of propagation.Keywords: Multilevel inverter, harmonic content, Grid-tie inverter